Ceramics for environmental and energy applications II - Dogan, Fatih; Tritt, Terry M.; Sekino, Tohru; Katoh, Yutai; Pyzik, Aleksander J.; Belharouak, Ilias; Boccaccini, Aldo R.; Marra, James; Lin, Hua Tay (wiley, 2014)
A collection of papers from the below symposia held during the 10th Pacific Rim Conference on Ceramic and Glass Technology (PacRim10), June 2-7, 2013, in Coronado, California 2012: Solid Oxide Fuel Cells and Hydrogen Technology Direct Thermal to Electrical Energy Conversion Materials and Applications Photovoltaic Materials and Technologies Ceramics for Next Generation Nuclear Energy Advances in Photocatalytic Materials for Energy and Environmental Applications Ceramics Enabling Environmental Protection: Clean Air and Water Advanced Materials and Technologies for Electrochemical Energy Storage Systems Glasses and Ceramics for Nuclear and Hazardous Waste Treatment.
CRIS-Team Scopus Importer:2022-08-05